Konsep Progresivisme Manajemen Pameran Prodi Pendidikan Seni Rupa UNISMUH Makassar : (Analisis Kajian Filsafat Pendidikan John Dewey) - Meisar Ashari; Soekarno B. Pasyah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research aims to explain the concept of progressivism in exhibition management in the Fine Arts Education study program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. The type of research used is qualitative-explanatory research, which provides an explanation of why fine arts education study programs use progressivism as a concept in exhibition management. This research uses a qualitative-explanatory method with a library research approach, namely providing an explanation by identifying several relevant literature, then filtering it based on the relevance and quality of the literature found. As a library research, the primary research data is in the form of John Dewey's progressivist philosophical thoughts in his primary work "Democracy and Education". Secondary data is in the form of a literature study of John Dewey's progressivist thoughts written in e-journals. The researcher documented the thoughts of educational progressivism according to John Dewey and then presented them descriptively.